Recent Developments of Leukemia in Children: A Literature Review - zahra, nisrina; Nastaghfiruka, Prita Aulia (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Childhood leukemia is one of the most common types of blood cancer in children. Despite advancements in treatment, challenges such as drug resistance and long-term side effects persist. Access to care remains a global issue. Objective: This systematic review aims to identify trends in childhood leukemia treatment, including novel therapies, challenges, and associated risk factors. Findings:Targeted therapy and immunotherapy have offered new hope in treating childhood leukemia. However, drug resistance remains a major challenge. Additionally, long- term side effects of intensive treatment, such as organ damage and increased risk of secondary cancers, need to be considered. Conclusion: Progress in treating childhood leukemia has yielded encouraging results. However, further research is still needed to overcome existing challenges. Future research should focus on developing more personalized therapies and gaining a deeper understanding of the genetic and environmental risk factors that contribute to the development of leukemia.